Eutrophication, harmful algae and biodiversity — Challenging paradigms in a world of complex nutrient changes. Issue 2 (30th November 2017) - Glibert, Patricia M.
Abstract: Eutrophication is a complex process and often associated with not only a change in overall algal biomass but also with a change in biodiversity. Common metrics of eutrophication (e.g., chlorophyll a ), total nitrogen (TN) and phosphorus (TP) are not adequate for understanding biodiversity changes, especially those associated with harmful algal bloom (HAB) proliferations. Harmful algae can increase disproportionately with eutrophication, depending on which nutrients change and in what proportion. This paper challenges several classic paradigms in our understanding of eutrophication and associated biodiversity changes. The underlying message is that nutrient proportions and forms can alter biodiversity, even when nutrients are at concentrations in excess of those considered limiting. The global HAB problem is on a trajectory for more blooms, more toxins, more often, in more places. Our approach to management of HABs and eutrophication must consider the broader complexity of nutrient effects at scales ranging from physiological to ecological. Highlights: Global nutrient loads are increasing; export of N is increasing faster than P. Proportions of nutrients affect HABs, their toxicity and the food web. Forms of N are also changing, affecting HABs, their biodiversity and toxicity. Classic dose-response models are insufficient for understanding, managing HABs. P control without N control has unintended consequences for HABs and the food web.